Polypharmacy and Drug–drug Interactions in Older and Younger People Living with HIV: The POPPY Study. Issue 3 (April 2019) - Halloran, Marie O; Boyle, Catherine; Kehoe, Brona; Bagkeris, Emmanouil; Mallon, Paddy; Post, Frank A; Vera, Jamie; Williams, Ian; Anderson, Jane; Winston, Alan; Sachikonye, Memory; Sabin, Caroline; et al.
Background: Polypharmacy (use of ≥ five medications) increases the risk of drug-drug interactions and can lead to negative health outcomes. This study aimed to review the medications of people living with HIV (PLWH) and HIV-negative controls in the POPPY study and evaluate the frequency of polypharmacy and potential drug-drug interactions (PDDIs). Methods: PDDIs between non-antiretroviral (ARV) drugs were analysed using the Lexicomp® database, and PDDIs between non-ARV and ARV drugs using the Liverpool drug interaction database. Between-group differences were assessed using χ 2, Mann-Whitney U and Kruskal-Wallis tests. Results: This analysis included 698 PLWH ≥50 years, 374 PLWH <50 years and 304 HIV-negative controls ≥50 years. The prevalence of polypharmacy was 65.8% in older PLWH, 48.1% in younger PLWH and 13.2% in the HIV-negative group. When ARVs were excluded, 29.8% of older PLWH and 14.2% of younger PLWH had polypharmacy. The prevalence of ≥1 PDDI involving non-ARV drugs was 36.1%, 20.3% and 16.4%, respectively, in older PLWH, younger PLWH and HIV-negative controls. In PLWH the prevalence of ≥1 PDDI involving ARV and non-ARV drugs was 57.3% in older PLWH and 32.4% in younger PLWH. Conclusions: Polypharmacy and PDDIs involving non-ARV/ARV drugs and non-ARV/non-ARV drugs were common among older PLWH, highlighting the need for increased awareness and additional research on all types of PDDI.